Rumen Fermentation Profiles of Protein-Energy Synchronization Index-Based Ration: an In Vitro Study - Afduha Nurus Syamsi; Merryafinola Ifani (Jurnal Ilmu Ternak dan Veteriner, 2023)
The study examined the effect of protein-energy synchronization (PES) index-based rations on the rumen fermentation profile. The material used was the Jawa Randu goat's rumen fluid, collected soon after the goat was slaughtered. The treatment ration consisted of elephant grass, lamtoro (Leucaena leucocephala), coconut meal, tofu waste, bran, cassava waste, and mineral mix arranged based on the PES index of each feed ingredient. The research was conducted in vitro using a completely randomized design (CRD). The treatment consisted of 4 PES indexes, namely 0.55 (R1); 0.6 (R2); 0.65 (R3); 0.7 (R4), and each had 5 replications. Data were analyzed by ANOVA and orthogonal polynomials (OP). The results of the ANOVA showed that the PES index did not affect the production of acetate (C2) and butyrate (C4) but had a highly significant effect on dry matter digestibility (DMD), organic matter digestibility (OMD), pH, a total of volatile fatty acids (VFA), propionate (C3), C2:C3 ratio, methane (CH4), ammonia (NH3), and microbial protein synthesis (MPS). The analysis of OP showed a quadratic effect on all variables with the equation Y= - 81.601X2 + 375.04X – 310.78  (DMD), Y= -433.69X2 + 522.69X – 128.75 (OMD), Y=-44X2 + 54.04X – 9.9 (pH), Y= -2160X2 + 2576.8X – 604.2 (VFA Total), Y= -481.8X2 + 585.01X – 143.45 (C3), Y = 50.93X2 – 60.177X + 21.067 (C2:C3), Y = 202.45X2 – 223.18X + 103.41 (CH4), Y= 436X2 – 552.28X + 181.08 (NH3), dan Y= -1012X2 + 1260X – 311.64 (MPS). Protein-energy synchronization (PES) index of 0.6 achieved the best rumen fermentability. The formulation of the PES index-based ration of 0.6 had the most effective compared to other indexes based on the high of propionate, the lowest methane, the lowest NH3, and the best microbial protein synthesis. The ration with an index of 0.6 is composed of 30% elephant grass, 30% Leucaena leucocephala, 10% coconut meal, 10% tofu waste, 10% rice brand, 9% cassava waste, and 1% mineral mix.